Community Resilience of Mining Area and Food Vulnerability in South Kalimantan - Nasdian, Fredian Tonny; Katrina Pandjaitan, Nurmala; Ardinal Barlan , Zessy (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2020)
Coal mining policies and activities in addition to having a positive impact on state income, job creation and business, also have a negative impact on ecosystems and communities in the mining area. The study was conducted in two mining communities in South Kalimantan using an emic and etic approach to explore community resilience and food insecurity due to ecological changes and the impact of mining policies and activities. Coal mining policies and activities in South Kalimantan causes catastrophic floods, land damage, and crop failure on lowland rice fields that have an impact on potential food insecurity at the household and community level. The pattern of community resilience in the two communities is in the form of social movements as a form of social adaptation, and agricultural land recovery and changing agricultural commodities as a form of ecological adaptation. The process of community resilience in the two communities is at the level of recovery towards a stable community condition, not yet at the transformation stage. Community capability is the most influential factor on the degree of community resilience so that the handling of food insecurity based on community resilience needs to be done by developing strategies to increase community capability.